1999
DOI: 10.1038/45154
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of spatial and nonspatial information in dorsal hippocampus

Abstract: The hippocampus in the mammalian brain is required for the encoding of current and the retention of past experience. Previous studies have shown that the hippocampus contains neurons that encode information required to perform spatial and nonspatial short-term memory tasks. A more detailed understanding of the functional anatomy of the hippocampus would provide important insight into how such encoding occurs. Here we show that hippocampal neurons in the rat are distributed anatomically in distinct segments alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
213
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(232 citation statements)
references
References 45 publications
15
213
2
2
Order By: Relevance
“…It is therefore possible that neighboring cells within the hippocampus might be arranged in the manner of the primary sensory cortices, with nearby cells sharing little overlap in place field location but significant overlap in other (as yet uncharacterized) functional variables (17). Consistent with this idea, Hampson et al (18) showed that neurons encoding task-relevant features of a delayed-non-match-to-sample task were distributed within defined segments of the hippocampus, providing evidence of a functional topography, at least along the septotemporal axis (18).…”
supporting
confidence: 68%
“…It is therefore possible that neighboring cells within the hippocampus might be arranged in the manner of the primary sensory cortices, with nearby cells sharing little overlap in place field location but significant overlap in other (as yet uncharacterized) functional variables (17). Consistent with this idea, Hampson et al (18) showed that neurons encoding task-relevant features of a delayed-non-match-to-sample task were distributed within defined segments of the hippocampus, providing evidence of a functional topography, at least along the septotemporal axis (18).…”
supporting
confidence: 68%
“…Those of us who have come into the field long after the acceptance of place cells can only imagine the surprise and disbelief that accompanied their initial discovery [14,142]. Although no one denies that under certain conditions, hippocampal pyramidal cells show spatial tuning curves (place fields), even today there are authors who argue that, dramatic though they may be, place fields are epiphenomena, a consequence of the spatial nature of experimental design [46,71,142,246].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
“…By this point, it is pretty much accepted that under certain conditions, hippocampal pyramidal cells show correlations to non-spatial aspects [48,69,71,101,109,157,238,239,246,247,250] (see [33,173] for reviews, but see [147] for an alternative viewpoint). These non-spatial aspects include when animals change task within an environment [101], in response to components of a task in which goals change [48,69,157,247], even after salient events [202].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this system may have originally evolved to support the storage, recall, and replay of routes, it is easy to see how it could have subsequently evolved to perform the same operations on experiences that are not explicitly topographical. In fact, cells have been discovered in the rat hippocampus that fire in response to nonspatial aspects of an episode Hampson et al, 1999). In the monkey hippocampus, ''spatial view cells'' have been discovered whose firing is correlated with where the monkey is looking rather than where the monkey is (Rolls et al, 1997).…”
Section: Medial Temporal Lobesmentioning
confidence: 99%